IMPLEMENTASI EMERGING PATERN UNTUK DATA COVID 19 PADA DKI JAKARTA - Ignatius Joko Dewanto; Ariya Panndhitthana Candra (Sekolah Tinggi Teknologi Informasi NIIT, 2021)
The research objective is to implement information on the covid 19 data mining pattern in the DKI Jakarta area. The problems faced are the difficulty in identifying the pattern of Covid 19 data in one area, it is difficult to digup data on the web http://corona.jakarta.go.id, then it is not easy to decide how to handle covid 19. This research method uses CRISP-DM with emerging patterns of supervision. and EPM Algoritm, the research contribution is to assist the Government in overcoming the problem of the spread of the covid 19 cluster in several regions in Indonesia. The results of the research resulted in a covid 19 information cluster in the DKI Jakarta environment